Case in Standard Arabic and Omani Arabic - Al-Balushi, Rashid (LANGUAGE ART, 2024)
This paper looks into the concept of structural case and its syntactic function, as well as into the verbal features that license structural nominative case to the subject and structural accusative case to the object in Standard Arabic. The paper includes a critique of some of the current approaches (proposed within generative linguistics) to the nature of those features. The paper then provides a new approach to account for the structural case facts in Standard Arabic. The paper also looks into the mechanism that Omani Arabic, a variety whose nouns do not inflect for case, uses to achieve the syntactic function of structural case. The paper then raises a question about this suggested mechanism in relation to Standard Arabic and provides a well-supported answer to it.